O fanzine e a leitura : a formação do autor-leitor no zinar - Hauch, Fabíola (2015)
This study presents the faces of reader formation in Zinar. Therefore, we seek to establish a theoretical framework on the genre fanzine to explain the reading on fanzine and the formation of the reader as the production and reception established by zinar, in addition to showing the possible reader profiles on fanzine. In order to support the concept of gender that this study intends and make use of the features described to show how the incursion occurs in the space of reading, two examples were analyzed: the Punhetão fanzine and the Ugra Zine Fest blog. As a result, we present the reader formation in the fanzine, that can be initial or continuing in zinar by author-reader's theory and through the wild readings. However, the reader's profile in those kind of space provides an interface between what is printed and what is in the cyberspace. We use as a theoretical framework for this research the postulates of Henrique Magalhães, Edgar Guimarães, Massimo Canevacci, Hakim Bey, Roger Chartier, Roland Barthes and Lucia Santaella